Association Between Late-Onset Leukoencephalopathy With Vanishing White Matter and Compound Heterozygous EIF2B5 Gene Mutations: A Case Report and Review of the Literature - Kong, Fanxin; Zheng, Haotao; Liu, Xuan; Lin, Songjun; Wang, Jianjun; Guo, Zhouke (Frontiers in Neurology, 2022)
Leukoencephalopathy with vanishing white matter (LVWM) is an autosomal recessive disease. Ovarioleukodystrophy is defined as LVWM in females showing signs or symptoms of gradual ovarian failure. We present a 38-year-old female with ovarioleukodystrophy who showed status epilepticus, gait instability, slurred speech, abdominal tendon hyperreflexia, and ovarian failure. Abnormal EEG, characteristic magnetic resonance, and unreported EIF2B5 compound heterozygous mutations (c.1016G>A (p.R339Q) and c.1157G>A (p.G386D)) were found. Furthermore, the present report summarizes 20 female patients with adult-onset ovarioleukodystrophy and EIF2B5 gene mutations. In conclusion, a new genetic locus for LVWM was discovered. Compared with previous cases, mutations at different EIF2B5 sites might have different clinical manifestations and obvious clinical heterogeneity.